2007
DOI: 10.1200/jco.2006.08.9607
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Outcome of Salvage Radiation Therapy for Recurrent Prostate Cancer After Radical Prostatectomy

Abstract: Nearly half of patients with recurrent prostate cancer after radical prostatectomy have a long-term PSA response to SRT when treatment is administered at the earliest sign of recurrence. The nomogram we developed predicts the outcome of SRT and should prove valuable for medical decision making for patients with a rising PSA level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
577
4
27

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 830 publications
(631 citation statements)
references
References 48 publications
22
577
4
27
Order By: Relevance
“…As observed in previous studies for SRT [25], our study seems to confirm that lower serum PSA level prior to salvage HIFU is a predictor of favorable response. Similarly, an increased percentage of high-grade RP Gleason scores (4ϩ3 or greater) was observed in the HIFU failure group compared with the success group (12.5% vs. 86%; P ϭ 0.01), suggesting that favorable Gleason Score could be associated with better outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…As observed in previous studies for SRT [25], our study seems to confirm that lower serum PSA level prior to salvage HIFU is a predictor of favorable response. Similarly, an increased percentage of high-grade RP Gleason scores (4ϩ3 or greater) was observed in the HIFU failure group compared with the success group (12.5% vs. 86%; P ϭ 0.01), suggesting that favorable Gleason Score could be associated with better outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…PSA kinetics can help identify these patients [22] but often involve multiple PSA measurements that can result in a delay of secondary therapy. Risk assessment tools that can accurately predict cancer recurrence and progression would allow a more timely institution of additional treatments that might be beneficial for selected patients [23][24][25]. Among the 109 published prediction tools [3], only 8 take advantage of pathologic information gained from RP, and very few of these tools have been validated.…”
Section: Discussionmentioning
confidence: 99%
“…Stephenson et al constructed a nomogram to predict the PSA response to salvage RT for BCR after RP [39]. The authors identified PSA levels before salvage RT, prostatectomy Gleason score, PSA DT, surgical margin status, lymph node involvement, and use of ADT with salvage RT as significant variables in the model.…”
Section: Salvage Treatment After Radical Prostatectomymentioning
confidence: 99%